Optimization of Inventory Costs Using the Continuous Review System (CRS) Method in Controlling the Need for Raw Materials for the Crimean Industry: Optimalisasi Biaya Persediaan Menggunakan Metode Continuous Review System (CRS) Dalam Pengendalian Kebutuhan Bahan Baku Industri Krimer - Varid Jainuri; Tedjo Sukmono (Academia Open, 2021)
Forecasting is an estimate of something that has not happened or will happen in the future. Determination of the policies implemented by the company resulted in more costs for storage costs, resulting in wastage of costs and reduced company profits due to the accumulation of capital in the form of raw materials that had not been produced. This study describes the planning and control of sodium caseinate inventory. Of the many inventory control planning methods, the continuous review system model is used to determine the optimal number of orders and when orders are made. The total cost of inventory based on average usage in 2018 to 2020 is IDR 252,323,882,141.00 per year. The results showed that the continuous review system lost sales inventory control model has a minimum total inventory cost of Rp. 251,641,850,991.00 per year with an optimal number of orders.